Gonadal Maturity Induction using Karamunting (Melastoma malabatrhicum) Ethanol Extract on White Shrimp Female (Litopenaeus vannamei) - Ridwan, Ahmad; Awaludin, Awaludin; Anggraeni, Tjandra (Proceeding International Conference on Global Resource Conservation, 2015)
Common problem that happened in white shrimp culturing is insufficiency of mature female to provide the seed simultaneously. There are several methods to accelerate gonadal maturity infemale white shrimp: eye ablation, environmental manipulation, and providing high cholesterol fresh feed. Till now, high cholesterol feed is not very common method. Karamunting or Malabar Melastome (Melasthoma malabatrhicum) is known to have a high cholesterol content, more specifically, lanosterol based on GCMS test. Lanosterol is cholesterol that contained in plants, which assumed as precursor hormone for gonad maturity process in female of white shrimp. The aim of this experiment is to determine whether Karamunting ethanol extract can stimulate and accelerate gonad development in female of white shrimp. This experiment consists of several steps: (1) Karamunting (Melastoma malabathricum) extraction, (2) GCMS test for Karamunting, (3) extract injection to female of white shrimp (Litopenaues vannamel) for 15 days in 3 days interval with dosage variable 0 (control), ), 10 mg/kg BW (P1), 7,5 mg/kg BW (P2), 5 mg/kg BW (P3), 2 mg/kg BW (P4) dan 1 mg/kg BW (P5), (4) The measuring parameters are Karamunting content, morphological gonad development observation and hepatopancreas somatic index (HSI)Â measurement, (5) Data analysis. Data shows that karamunting ethanol extract with P1 and P2 dosage can result in morphological gonad development response (GML II), meanwhile with P3, P4 and P5 dosage there is no changes observed. All variables didnât affect the level of HSI (P>0.05). Based on the result, it can be concluded that Karamunting ethanol extract indicates an acceleration of gonad maturity process in white shrimp female.Keywords : Gonad maturity; Hepatopancreas Somatic IndexÂ ; L.Â vannamei; M. malabatrhicum